What makes motion dazzle markings effective against predation?. (27th September 2019) - Kodandaramaiah, Ullasa; Palathingal, Shuaib; Bindu Kurup, Gayathri; Murali, Gopal
Abstract: Motion dazzle markings comprise patterns such as stripes and zig-zags that are postulated to protect moving prey by making predators misjudge the prey's speed or trajectory. Recent experiments have provided conflicting results on their effect on speed perception and attack success. We focus on motion dazzle stripes and investigate the influence of four parameters—stripe orientation, stripe contrast, target size, and target speed—on perceived speed and attack success using a common experimental paradigm involving human "predators" attacking virtual moving targets on a computer touchscreen. We found that high-contrast stripes running parallel or perpendicular to the direction of motion reduce attack success compared to conspicuous uniform targets. Surprisingly, parallel stripes induced underestimation of speed, while perpendicular stripes induced overestimation of speed in relation to uniform black, suggesting that misjudgment of speed per se is sufficient to reduce attack accuracy. Across all the experiments, we found some support for parallel stripes inducing underestimation of target speed but these stripes reduced attack success only when targets were small, moved at an intermediate speed, and had high internal contrast. We suggest that prey features (e.g., size or speed) are an important determinant of capture success and that distortion of speed perception by a color pattern does not necessarily translate to reduced capture success of the prey. Overall, our results support the idea that striped patterns in prey animals can reduce capture in motion but are effective under a limited set of conditions. Lay Summary: We show that target and color pattern characteristics are important determinants for the effectiveness of motion dazzle colorations—repetitive color patterns that are proposed to reduce predatory attacks when the prey is moving. Experimental results from previous studies have been highly inconsistent, often strongly conflicting with each other, one reason for this being differences in the experimental protocols followed. We conduct a large set of experiments to understand the important determinants of the effectiveness of motion dazzle colorations.